Diode laser as local treatment for oral Kaposi's sarcoma in HIV young patient: a case report - Lombardi Niccolò; Varoni Elena; Moneghini Laura; Lodi Giovanni (EDP Sciences, 2021)
Introduction: Kaposi's sarcoma (KS) is a malignant mucocutaneous neoplasm caused by human herpesvirus 8 (HHV-8). Four types of KS exist and, in each of them, the patient could develop skin and visceral lesions. Surgical excision, radiotherapy, intralesional chemotherapy and systemic chemotherapy are widely accepted as treatment options. Observation: The aim of this paper is to present diode laser as minimally invasive procedure in management of oral KS. We report here a case of multiple oral lesions of acquired immunodeficiency syndrome (AIDS)-associated KS, which has been solely treated with diode laser. Discussion: There is no bibliography on local treatment of oral KS with diode laser and this clinical case appears to be the first regarding this technique. Conclusion: This conservative approach, in association with highly active antiretroviral therapy (HAART), is safe and effective, shows fewer side effects than chemotherapy, radiotherapy and surgical excision and may be evaluated as potential treatment for oral KS.